Sexual Development of Silba adipata (Diptera: Lonchaeidae): Effects of Diet, Ultraviolet Light and Fig Latex - Ricardo Díaz-del-Castillo; Guadalupe Córdova-García; Diana Pérez-Staples; Andrea Birke; Trevor Williams; Rodrigo Lasa (Insects)
The black fig fly, Silba adipata McAlpine (Diptera: Lonchaeidae), is a monophagous invasive pest of fig crops. Its recent detection in Mexico has highlighted the urgent need for control strategies. However, efforts to study and manage this pest are constrained by a limited understanding of its basic biology and an inability to rear this insect in the laboratory. Some species of flies are reproductively immature at adult emergence and require specific nutrients for the development of reproductive structures. Given this, we examined the development of ovaries and testes in response to different adult diets, ovary maturation in relation to access to figs and ultraviolet (UV) light exposure and behavioral responses to fig latex. Dietary protein (hydrolyzed yeast) was essential for egg maturation. The highest prevalence of sexual maturity in females was observed at age 21 days and was not influenced by UV light or access to figs. Male testes size decreased over time irrespective of the adult diet. The consumption of latex increased when protein was not available, although the sexes differed in their response to latex over time. These findings help overcome a critical barrier to the laboratory colonization of S. adipata by demonstrating that protein-supplemented diets are essential for sexual maturation. However, the lack of information on the specific role of fig latex in the diet and the absence of sexual behavior during the experiments highlight key knowledge gaps. Future research should focus on identifying those stimuli that promote copulation and oviposition to understand the complete life cycle of this pest under controlled conditions.